Evaluation of surface roughness and color stabilityof a nanohybrid resin subjected to diferent salivary pH - Andrango Herrera, Geovanna (2021)
Objective: To determine the surface roughness and color stability of a nanohybrid resin subjected to different salivary pH at different times. Materials and methods: experimental, comparative, in vitro study, in which 45 discs of EA2 nanohybrid resin (OPALLIS FGM), and randomly distributed in three groups (n = 15). Each discs was subjected to an evaluation of its roughness by means of a digital roughness meter (TESTER SRT-6200) and color by colorimeter (Tooth Color Comparator). The discs according to their the group was immersed in 18ml of artificial saliva modified with citric acid until obtaining saliva of pH 5, 6 and 7 respectively, maintained at 37 ° C, according to the specifications of the ANSI / ADA No. 66 standard. After 168 and 504 hours of storage, a second and third evaluation, respectively, of roughness and color, was carried out. Statistical system using the Friedman and Kruskal Wallis test Results: The three salivary pHs modified the surface roughness of the material used in a more evident way, pH 5, observing an increase in surface roughness with the time of exposure to substances with different pH analyzed (p <0.01), the color showed an evident increase of 4 tones in all the samples, with an evident difficulty to analyze statistically. Conclusions: The increase in roughness was proportional with time and inversely proportional with the pH, more evident with pH5, the color evaluation mechanism did not allow obtaining a conclusive data.